Application of Information Technology in Islamic Boarding Schools in Indonesia - Abdurrahman Iskandar; Mohamad Hasan Nurrahmat (International journal of technology and education research, 2026)
Background: The development of information technology has driven transformation in Islamic boarding schools in the aspects of learning, administration, and da'wah, but its implementation still faces obstacles in infrastructure and digital literacy. Objective: This study reviews the implementation of information technology in Islamic boarding schools to formulate an applicable IT development roadmap. Type and method: This study is a systematic literature review that collects and synthesizes secondary studies related to the application of IT in Islamic boarding schools. Population and sample: The population consists of academic literature and practice reports from the most recent period; the sample was selected based on the inclusion criteria of relevance and methodological quality. Data analysis instruments and techniques: The main instrument is a data extraction sheet; the analysis technique uses thematic narrative synthesis to identify patterns of benefits, challenges, and solutions. Research results: The results show three main benefit domains: digitalization of learning that increases access and effectiveness, a pesantren management system that speeds up administration and improves accountability, and the use of websites and social media to expand the reach of da'wah; obstacles include limited infrastructure, low digital literacy of teachers and students, and limited funding. Conclusion: Adoption of IT in Islamic boarding schools promises to improve the quality of education and operational efficiency but requires infrastructure improvement strategies, digital literacy training programs, clear IT governance, and partnerships for funding for sustainable implementation.